Exchange Rate Changes and Trade Balance: An Empirical Study of the Case of Japan - SHAO, Ziwei (Institutional Knowledge at Singapore Management University, 2008)
This paper attempts to identify the major economic factors that influence the bilateral trade balance between Japan and the US. Differing from conventional elasticities approach, one more variable--the net foreign assets--is added in the Vector Autoregression estimation using quarterly data from 1980: I to 2006: IV. The Johansen and Juselius result indicates three long-run relationships among five macro variables: trade balance, domestic income, foreign income, net foreign assets and real exchange rate. Short run adjustment parameters are identified as coefficients of the error correction terms. The variance in trade balance due to variations in the two macro variables--the exchange rate and the net foreign assets--is examined by Impulse Response Functions and Variance Decomposition procedures. The main finding of this paper is that taking the valuation effect of the net foreign asset position into account, the final effect of the exchange rate changes on trade balance is undetermined. Although appreciation can reduce trade surplus in the short run, in a longer horizon, there is no stable relationship. The positive sign of the relation is not guaranteed in this case, and appreciation is not surely able to correct the trade imbalance between countries.